2017
DOI: 10.5271/sjweh.3654
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationships between job strain and low-back pain

Abstract: Temporal relationships between job strain and low-back pain by Magnusson Hanson LL, Madsen IEH, Rugulies R, Peristera P, Westerlund H, Descatha A To our knowledge this is one of the first studies to examine reciprocal relationships between job strain and back pain and which accounts for time-invariant characteristics. The study highlights a need for more work to establish if there are bidirectional relationships, with more frequent repeat measurements and which account for time-stable individual factors. Origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Substantial research evidence from northern European countries has demonstrated significant associations between job strain and back pain. A study based on the Swedish Longitudinal Occupational Survey of Health (SLOSH) indicated that job strain was associated with increased back pain severity 35 . A study of the Swiss working population based on the Fourth European Working Conditions Survey (EWCS) reported that physical or psychological demanding jobs were associated with higher prevalence of back pain 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research evidence from northern European countries has demonstrated significant associations between job strain and back pain. A study based on the Swedish Longitudinal Occupational Survey of Health (SLOSH) indicated that job strain was associated with increased back pain severity 35 . A study of the Swiss working population based on the Fourth European Working Conditions Survey (EWCS) reported that physical or psychological demanding jobs were associated with higher prevalence of back pain 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The other reasons for exclusion are reported within the PRISMA flow diagram (Figure 1). Following the fulltext screening, a total of 47 articles were included in the study, as shown in Figure 1 (Andersen et al, 2019;Bodin et al, 2018;Bovenzi, 2009Bovenzi, , 2015Bovenzi et al, 2015Bovenzi et al, , 2016Christensen et al, 2018;Christensen & Knardahl, 2010Clausen et al, 2013;Dragioti et al, 2019;Garg et al, 2012Garg et al, , 2014Gerr et al, 2014;Halonen et al, 2018Halonen et al, , 2019Harris et al, 2011;Herin et al, 2012Herin et al, , 2014Hooftman et al, 2009;Hush et al, 2009;Janssens et al, 2014;Jun et al, 2020;Kaaria et al, 2011;Lamy et al, 2014;Lapointe et al, 2009Lapointe et al, , 2013Larsman et al, 2011;Larsman & Hanse, 2009a, 2009Lu et al, 2014;Madsen et al, 2018; Magnusson Hanson et al, 2017;Matsudaira et al, 2012;Mierswa & Kellmann, 2017;Oakman et al, 2017;Plouvier et al, 2009;Prakash et al, 2017;…”
Section: Resultsmentioning
confidence: 99%
“…The other reasons for exclusion are reported within the PRISMA flow diagram (Figure 1). Following the full-text screening, a total of 47 articles were included in the study, as shown in Figure 1 (Andersen et al, 2019; Bodin et al, 2018; Bovenzi, 2009, 2015; Bovenzi et al, 2015, 2016; Christensen et al, 2018; Christensen & Knardahl, 2010, 2014; Clausen et al, 2013; Dragioti et al, 2019; Garg et al, 2012, 2014; Gerr et al, 2014; Halonen et al, 2018, 2019; Harris et al, 2011; Herin et al, 2012, 2014; Hooftman et al, 2009; Hush et al, 2009; Janssens et al, 2014; Jun et al, 2020; Kaaria et al, 2011; Lamy et al, 2014; Lapointe et al, 2009, 2013; Larsman et al, 2011; Larsman & Hanse, 2009a, 2009; Lu et al, 2014; Madsen et al, 2018; Magnusson Hanson et al, 2017; Matsudaira et al, 2012; Mierswa & Kellmann, 2017; Neupane & Nygard, 2017; Oakman et al, 2017; Plouvier et al, 2009; Prakash et al, 2017; Shahidi et al, 2015; Smith et al, 2009; Solidaki et al, 2013; Vandergrift et al, 2012; Van Nieuwenhuyse et al, 2013; Vargas-Prada et al, 2013, 2016; Wigaeus Tornqvist et al, 2009). Most studies were conducted in Europe ( n = 34, 72%), followed by the Americas ( n = 10, 21%) and Asia/Australia ( n = 3, 7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Scandinavian Journal of Work, Environment & Health, Magnusson Hanson and colleagues address this topic with a novel approach by combining structural equation modelling (SEM) with a fixed-effects (FE) regression in a longitudinal study with four waves over a 6-year period (7).…”
mentioning
confidence: 99%